Penerapan Sistem Pencatatan Keuangan Pada UMKM Donat Bunda Al Di Surabaya - Eka Faricha Bachrie; Nadia Rachmawati; Salsabilah Al Fitri; Nur Laili Rahmawati; Dia Nur Aini; Mochamad Reza Adiyanto (Jurnal Riset Akuntansi, 2024)
This research discusses the importance of Micro, Small, and Medium Enterprises (MSMEs) in the Indonesian economy, especially in creating jobs, increasing national income, and reducing unemployment and poverty. Despite their significant contribution, MSMEs often face obstacles in financial management, especially in effective financial recording and reporting. As a case study, this research focuses on Bunda Al's donut business in Surabaya which is experiencing challenges in financial recording due to the business owner's lack of understanding about accounting. This research aims to identify ways to improve the financial management of MSMEs through basic accounting training and the use of simple accounting systems such as Microsoft Excel or Google Sheets. The main focus includes practices to manage finances in a healthy and sustainable manner, including recording daily transactions, preparing necessary financial reports, and ensuring the accuracy of financial reports. The research method involved interviews with MSME owners and descriptive analysis to characterize the data. The results showed that effective financial management starts with the selection of quality raw materials and accurate recording of daily transactions. Businesses are advised to expand their financial statements to include balance sheets and cash flows for a more complete financial picture. This research is expected to provide practical guidance for MSMEs in improving their financial management, as well as encourage the effective application of accounting principles. Thus, improving the quality of accounting records is expected to contribute to innovation in accounting science and its application among MSMEs.